Comparison between Itraconazole and Cotrimoxazole in the Treatment of Paracoccidiodomycosis - Cavalcante, Ricardo de Souza [UNESP]; Sylvestre, Tatiane Fernanda [UNESP]; Levorato, Adriele Dandara [UNESP]; Carvalho, Lidia Rachel de [UNESP]; Mendes, Rinaldo Poncio [UNESP] (Public Library Science, 2014)
BackgroundThere are no published reports on studies comparing itraconazole (ITC), sulfamethoxazole-trimethoprim (cotrimoxazole, CMX), and ITC followed by CMX (ITC/CMX) in the treatment of paracoccidiodomycosis. This study aimed to compare the efficacy, effectiveness, safety and time to clinical and serologic cure in paracoccidioidomycosis patients treated with ITC or CMX, the antifungal agents most widely used.MethodologyA quasi-experimental study was performed in 177 patients with a confirmed or probable diagnosis of paracoccidioidomycosis. Treatment was divided into two stages: 1) initial, which was continued until clinical cure was achieved and the erythrocyte sedimentation rate decreased to normal values; 2) complementary, which was continued until serologic cure was achieved. Medians were compared via the Mann-Whitney test, and frequencies were compared via the chi-squared test. The assessment of variables as a function of time was performed using Kaplan-Meier curves and Cox regression. The significance level was established as p <= 0.05.Principal FindingsNo difference was found in the efficacy and effectiveness of the initial treatment of 47 individuals given ITC and 130 individuals given CMX; however, the time to clinical cure was shorter in the former compared with the latter group (105 vs. 159 days; p = 0.001), specifically in patients with the chronic form. Efficacy and effectiveness of the three regimens were similar in the complementary treatment; however, the time to serologic cure was shorter when ITC (161 days) or CMX (495 days) was used compared with ITC/CMX (881 days) [p = 0.02]. The independent predictors of a shorter time to serologic cure were treatment with ITC [risk ratio = 6.61 (2.01-21.75)] or with CMX [risk ratio = 5.11 (1.91-13.67)]). The prevalence of side effects was lower with ITC (6.4%) than with CMX (20.0%; p = 0.03).ConclusionsSince ITC induced earlier clinical cure and was better tolerated than CMX, such triazole should be considered the first-choice for PCM treatment.